P336Exome sequencing of multiple affected individuals from an Irish family with Brugada Syndrome uncovers a novel locus for the disorder. (15th July 2014) - Barc, J G; Marsman, RF; Marsman, RF; Le Scouarnec, S; Le Scouarnec, S; Mizusawa, Y; Mizusawa, Y; Lindenbaum, P; Lindenbaum, P; Carter, N; Carter, N; Redon, R; et al.
Abstract: Introduction: Brugada Syndrome (BrS) is a disorder associated with an increased risk of sudden cardiac death and specific ECG features consisting of ST-segment elevation in the right precordial leads. Loss-of-function mutations in SCN5A underlie the disorder in ∼25% of patients. While other genes have been implicated, these account for <1% of subjects. Thus the genetic basis of BrS remains unknown in the majority of cases. We here set out to identify the genetic defect underlying BrS in a 3 generation family from Ireland with a case of spontaneous type 1 ECG who died suddenly at 24 years old. Methods: Exome sequencing was carried out in 3 individuals from the pedigree using Agilent SureSelect Target Enrichment 50Mb capture followed by sequencing on an Illumina HiSeq 2000. These 3 individuals were selected based on their genetic distance and the presentation of a BrS ECG at baseline. Results: Comparison of 3 exomes from affected individuals identified 22, 171 shared variants. Filtering out of variants occurring at a minor allele frequency (MAF) of >1% in public and in-house exome/genome databases, and considering all types of exonic variants and splice site variants, resulted in 10 rare variants shared among the 3 affected. Two of the variants are found in all afffected family members and not in the unaffected and reside in 2 different genes, namely HOOK3 and PXDNL. These 2 variants have been found at a MAF of 0.02% and 0.008%, respectively, in the NHLBI Exome Variant Project population (n=6500 individuals). The function of PXDNL, which appears to be specifically expressed in heart, is yet unknown. The PXDNL variant is predicted to be deleterious and probably damaging by SIFT and Polyphen2 algorithms, respectively. Conclusions: We identified by exome sequencing a chromosomal interval and a possible novel gene for BrS. Ongoing functional studies are aimed at investigating further the involvement of this gene in the BrS.